Propuesta para la reutilización el agua residual tratada en una empresa de cereales en la ciudad de Bogotá (2017)
This cereal-producing company identified with economic activity code N ° 0115, located in the industrial area of Montevideo in Bogotá city, since 1970 is dedicated to manufacturing and distributing products such as cereals of different types and cereal bars. In its processes the use of drinking water is quite considerable, reaching an average of 800 m³ per month only within the production plant, where 100% of this comes from the EAAB (Empresa de Acueducto y Alcantarillado de Bogotá).